Penetrasi Konsep Hibah Sebagai Solusi Dalam Proses Pembagian Waris - Diana Farid; Muhammad Husni Abdulah Pakarti (al-Battar: Jurnal Pamungkas Hukum, 2024)
An owner of property has the right to make grants to anyone, including his children, provided that the grant does not reduce the inheritance rights of other heirs. Grants that are given with the right conditions and fulfilled pillars are valid in law. However, there are restrictions in Islamic law regarding the granting of grants to heirs. This research aims to analyze the rights of heirs to grants and the limits of granting grants in Islamic law, Customary Law, and the Civil Code (BW), especially related to the protection of the rights of heirs. This research uses the literature study method by analyzing relevant legal sources, such as Islamic Law, Customary Law, and BW, to understand the provisions on grants and the division of inheritance. Grants given to heirs do not reduce their inheritance rights, as long as the grant does not exceed the stipulated limit, which is a maximum of 1/3 of the grantor's assets. This aims to protect the rights of heirs who could potentially be harmed by excessive grants. In addition, the principle of justice must be applied when grants are given to children or other heirs, to avoid imbalances in the distribution of inheritance. The maximum grant restrictions in Islamic Law, Customary Law, and BW aim to maintain the balance of heirs' rights and prevent harm to them. Although grants can strengthen relationships, it is important to comply with the legal limits to ensure that the rights of the heirs are not compromised. The existence of such restrictions also demonstrates the need for caution in making grants, especially when the grantor passes away and the distribution of the inheritance must be done.